Placenta accreta spectrum disorders in twin pregnancies as an under reported clinical entity: a case series and systematic review. (12th December 2022) - Cali, Giuseppe; Labate, Francesco; Cucinella, Gaspare; Fabio, Manuela; Buca, Danilo; Di Girolamo, Raffaella; Khalil, Asma; D'Antonio, Francesco
Abstract: Recent reports suggested a potential association between twin pregnancy and the occurrence of placenta accreta spectrum (PAS) disorders. Despite this, scarce data on PAS disorders in twins has been reported in the published literature. We present a series of twelve twin pregnancies complicated by PAS from two large institutions over 5 years. A systematic review of the literature was also conducted in order to find studies reporting on the risk factors, prenatal diagnosis using ultrasound and clinical outcomes of PAS in twin pregnancies.